System design and application for evaluation of digging agility in college male volleyball players - Ho, C.-S.; Lin, K.-C.; Hung, M.-H.; Chang, C.-Y.; Chen, K.-C. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2019)
The primary objective of this study was to design a digging agility system that was used to analyze the effectiveness of 6 weeks of plyometric training on volleyball players. A total of 24 highly trained college male volleyball players were recruited for this study. The players were equally divided into a plyometric training group and a control group. The agility T-test, peak power output test, 10-meter sprint, and digging agility test were used to examine the effects of plyometric training on the digging agility of volleyball players. One-way analysis of covariance was conducted to examine the differences in the variables between groups. The results reveal that after 6 weeks of plyometric training, the plyometric training group had significant improvements on the agility T-test, digging agility test, and peak power output tests, with statistical power values all greater than 90%. The plyometric training group significantly improved by 2.68% on the agility T-test, 2.35% on the digging agility test, and 7.32% on the peak power output test. The results indicated that appropriate plyometric training can enhance the agility of lateral movements and peak output of vertical jumps, as well as enable players to rapidly complete movements during a moving defense.